Komunikasi Pembelajaran dan Pembentukan Kepribadian Positif dalam Al-Quran - MS, Farizal (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2022)
The development of civilization in Indonesia is still colored by negative moral behavior, especially in communication, such as the expression of netizens responding to news. The increasing number of cases of corruption, violence and criminal cases shows very immoral behavior that affects social interaction, community communication and behavior change. So that this behavior is a characteristic of a person's personality, which in the formation of his personality can only start from the golden age (Golden Age) to adulthood. Therefore, this paper reminds us of the need for competence of teachers/educators in communicating with students in forming a positive personality reciprocally, both at home and in educational institutions. Several ways can be done by parents of students as primary educators or teachers in order to form a positive personality in students. So this can be done in several ways, including: In teaching students, educators are ethical in communicating, teaching them by concrete examples, individuals who behave positively in advising, teaching them about emotional intelligence, punishment and reward programs are implemented, storytelling methods in teaching Introducing the noble value of human relations with the Creator, supervising social relations, supervising students in the use of internet technology. It is hoped that with the application of communication ethics in the Qur'an which is a reference for parents and educators, students will someday be able to have positive personality traits